2013
DOI: 10.1088/0004-637x/765/1/73
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of X-Ray Emission From Young Suns in the Small Magellanic Cloud

Abstract: We report the discovery of extended X-ray emission within the young star cluster NGC 602a in the Wing of the Small Magellanic Cloud (SMC) based on observations obtained with the Chandra X-ray Observatory. X-ray emission is detected from the cluster core area with the highest stellar density and from a dusty ridge surrounding the H ii region. We use a census of massive stars in the cluster to demonstrate that a cluster wind or wind-blown bubble is unlikely to provide a significant contribution to the X-ray emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 94 publications
7
17
0
Order By: Relevance
“…An independent sign of the young ages of the PMS stars identified by the cyan contour lines in Figure 8 comes from X-ray observations. The distribution of our young PMS stars agrees rather well with the extended X-ray emission measured by Oskinova et al (2013) in this field using Chandra. For ease of comparison, we show in Figure 9 the areas of extended Xray emission by means of the contour levels (orange lines) obtained by Oskinova et al (2013), together with an intensity FIG.…”
Section: Younger Pms Starssupporting
confidence: 85%
See 2 more Smart Citations
“…An independent sign of the young ages of the PMS stars identified by the cyan contour lines in Figure 8 comes from X-ray observations. The distribution of our young PMS stars agrees rather well with the extended X-ray emission measured by Oskinova et al (2013) in this field using Chandra. For ease of comparison, we show in Figure 9 the areas of extended Xray emission by means of the contour levels (orange lines) obtained by Oskinova et al (2013), together with an intensity FIG.…”
Section: Younger Pms Starssupporting
confidence: 85%
“…The distribution of our young PMS stars agrees rather well with the extended X-ray emission measured by Oskinova et al (2013) in this field using Chandra. For ease of comparison, we show in Figure 9 the areas of extended Xray emission by means of the contour levels (orange lines) obtained by Oskinova et al (2013), together with an intensity FIG. 9.-Same as Figure 8, but the underlying Hα image is shown in negative, on a grey scale.…”
Section: Younger Pms Starssupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, AB 8 is the only WR binary in our sample not detected in X-rays. The star was in the field of view of Chandra and XMM-Newton observations (Oskinova et al 2013), but only an upper limit of 5 × 10 32 erg s −1 could be established for its X-ray luminosity. Given the very strong wind of the primary, it is difficult to explain such a low X-ray luminosity; Zhekov & Skinner (2015) recently reported that the X-ray luminosity of the Galactic WO binary WR 30a is >10 The terminal velocity of the companion is found to be comparable to that of the primary.…”
Section: Appendix A: Comments On Individual Targetsmentioning
confidence: 99%
“…The BeXRB binary SXP 1062 was discovered by Hénault-Brunet et al (2012) using Chandra and XMM-Newton observations of the star-forming region NGC 602 (Oskinova et al 2013b). Amongst other BeXRBs in the SMC, SXP 1062 is outstanding owing to: (i) The position in the wing of the SMC, where a younger stellar population is found and less BeXRBs are known compared to the bar of the SMC.…”
Section: Introductionmentioning
confidence: 99%